Influence of pregnancy on cardiac function and hemodynamics in women with Ebstein's anomaly. (8th June 2018) - Kanoh, Miki; Inai, Kei; Shinohara, Tokuko; Shimada, Eriko; Shimizu, Mikiko; Tomimatsu, Hirofumi; Ogawa, Masaki; Nakanishi, Toshio
Abstract: Introduction: We examined the perinatal outcomes and right ventricular function before pregnancy, during pregnancy, and after delivery in women with Ebstein's anomaly. Material and methods: We retrospectively investigated the clinical course and mode of delivery and monitored hemodynamic parameters throughout pregnancy in 17 women with Ebstein's anomaly who delivered at our institution during the period of 1995–2015. Results: Eight women, including nine pregnancies, underwent elective cesarean section, and nine women, including 14 pregnancies, underwent vaginal delivery. Elective cesarean section was performed in cases with significant heart failure or arrhythmias and in the presence of more than two of the following: cardiothoracic ratio ≥60%, moderate or severe tricuspid valve regurgitation, tricuspid valve regurgitation pressure gradient ≥35 mmHg during pregnancy. The cardiothoracic ratio and tricuspid valve regurgitation pressure gradient significantly increased during pregnancy compared with prepregnancy values. The New York Heart Association classification deteriorated from class I to class II or III in five cases during pregnancy. Conclusions: Although pregnancy was relatively safe among women with Ebstein's anomaly, some women developed cyanosis, arrhythmia, and heart failure, leading to elective cesarean section. Monitoring clinical and hemodynamic changes throughout pregnancy is advised to minimize maternal cardiac risk and select the appropriate mode of delivery.